Pilot community‐mobilization program reduces maternal and perinatal mortality and prevents obstetric fistula in Niger. Issue 3 (31st July 2014) - Seim, Anders R.; Alassoum, Zeidou; Bronzan, Rachel N.; Mainassara, Abderhamane Alou; Jacobsen, Judith L.; Gali, Yaroh Asma
Abstract: Objective: To assess the impact of a pilot community‐mobilization program on maternal and perinatal mortality and obstetric fistula in Niger. Methods: In the program, village volunteers identify and evacuate women with protracted labor, provide education, and collect data on pregnancies, births, and deaths. These data were used to calculate the reduction in maternal mortality, perinatal mortality, and obstetric fistula in the program area from July 2008 to June 2011. Results: The birth‐related maternal mortality fell by 73.0% between years 1 and 3 ( P < 0.001), from 630 (95% confidence interval [CI] 448–861) to 170 (95% CI 85–305) deaths per 100 000 births. Early perinatal mortality fell by 61.5% ( P < 0.001), from 35 (95% CI 31–40) to 13 (95% CI 10–16) deaths per 1000 births. No deaths due to obstructed labor were reported after the lead‐in period (February to June 2008). Seven cases of community‐acquired fistula were reported between February 2008 and July 2009; from August 2009 to June 2011 (23 months; 12 254 births), no cases were recorded. Conclusion: Community mobilization helped to prevent obstetric fistula and birth‐related deaths of women and infants in a large, remote, resource‐poor area.